An adaptive te-pv hybrid energy harvesting system for self-powered iot sensor applications - Mishu M.K.; Rokonuzzaman M.; Pasupuleti J.; Shakeri M.; Rahman K.S.; Binzaid S.; Tiong S.K.; Amin N. (MDPI AG, 2023)
Energy harvesting; Wireless sensor networks; Complete system; Data transmission intervals; Internet of Things (IOT); Minimum temperature differences; Sensor applications; Smart-phone applications; Temperature differences; Wireless sensor network (WSNs); Internet of things